Congenital Nasal Pyriform Aperture Stenosis: Same CT Dimensions, Varied Scenarios - Naina, Picardo; Dahiya, Vijeyta; Irodi, Aparna; Varghese, Ajoy Mathew (Indian Journal of Radiology and Imaging, 2022)
Congenital nasal pyriform aperture stenosis (CNPAS) is a rare cause of neonatal respiratory distress. We report a case series of four infants with similar radiological dimensions but while two needed surgery, two could be managed conservatively. The clinical presentation of the child and the response to conservative treatment, rather than the radiological dimensions were the main predictors for surgical intervention.
Keywords: congenital nasal pyriform aperture stenosis; infants; radiology; CT PNS; sub labial approach; endoscopic approach